Upaya Peningkatan Minat Belajar Siswa Melalui Nilai – Nilai Kecerdasan Spiritual - Siti Maftuhah; Irman Irman (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
The world of education as a center to form good and quality human resources is not only in terms of intelligence but emotionally and spiritually. The role of experts in the world of education is very important in the formation of quality human resources. The value of spiritual intelligence that is believed to be an intellectual and emotional balance, builds life to be more meaningful and have psychological calm. Making students the best individuals, in all aspects, one of which is in the learning process. Interest in learning as one aspect in achieving good results. So this study aims to examine efforts to increase student interest in learning through spirtual intelligence values, using descriptive qualitative research in grade 3 students of Mts Darunna'im, with data collection techniques through observation, interviews and documentation also supported by the results of primary and secondary data analysis. Producing spiritual intelligence values owned by students is very effective and has an effect on efforts to increase interest in learning.